PRODUCTION PLANNING AND SCHEDULING FOR LOT PROCESSING - BURTSEVA, LARYSA. WERNER, FRANK. ROMERO-PARRA, RAINIER (CAMBRIDGE SCHOLARS PUBLIS, 2022)
This book is dedicated to questions of production planning and scheduling activities both in general and in semiconductor manufacturing environments, which have the characteristics of high volume and high mixture. It explores topics such as shop models, work-in-process management, the treatment of setup times, basic techniques of lot batching and splitting, lot sizing and group technology approaches, as well as rescheduling questions. A number of directions for further research is suggested in the book, and a broad collection of references is provided.